Better decision-making skills support tactical behaviour and reduce physical wear under physical fatigue in soccer - Dambroz, Felipe; Teoldo, Israel (Frontiers in Physiology, 2023)
The purpose of this study was to verify whether decision-making skills influence the tactical behavior and physical performance of soccer players under acute physical fatigue, assessed in an actual game-play. The sample was comprised of 24 trained soccer players (18.25 ± 1.48 years old) from two Brazilian clubs grouped into two categories with 12 players each (with high and low decision-making skills). The assessment of decision making, tactical behavior, and physical performance were carried out using TacticUP®, FUT-SAT, and GPSports®, respectively. Acute physical fatigue was induced through the T-SAFT90 test. Results showed that under acute physical fatigue players with high decision-making skills maintained tactical behavior efficiency and had their paces reduced, in addition to displaying reduced total distance covered (p < 0.001), number of accelerations (p < 0.001), and decelerations (p < 0.001), and average movement speed (p < 0.001). On the other hand, players with low decision-making skills displayed reduced tactical behavior efficiency (p = 0.002) and maintained their movement pace under physical fatigue. It is concluded that decision-making skills contribute to players’ tactical behavior efficiency under acute physical fatigue, besides promoting reduced physical strain in movement actions throughout the field.